Melt surface deformation during stainless steel laser cutting in vacuum and atmospheric pressure - Aggoune, Samia; ., .; ., . (International Journal of Engineering and Technology, 2018)
The analysis of the recoil pressure generated during stainless steel laser beam irradiation is carried out. The threshold temperature from which the melted surface begins to be  deformed is investigated. The corresponding melt expulsion velocity in vacuum and at atmospheric pressure is evaluated. We demonstrate that the recoil pressure contributes weakly to the lateral ejection of the molten material if the surface temperature is equal or is lower than that of the vaporization one at atmospheric pressure. This recoil pressure causes expulsion only only for surface temperatures which are very higher than the boiling point; this conclusion is not valid in vacuum. It is also shown that  the initial stage of liquid metal ejection can be predicted by balancing the vapor recoil force with the surface tension force at the periphery of the liquid pool.